1996
DOI: 10.1080/10473289.1996.10467492
|View full text |Cite
|
Sign up to set email alerts
|

A Fuel-Based Motor Vehicle Emission Inventory

Abstract: A fuel-based methodology for calculating motor vehicle emission inventories is presented. In the fuel-based method, emission factors are normalized to fuel consumption and expressed as grams of pollutant emitted per gallon of gasoline burned. Fleet-average emission factors are calculated from the measured on-road emissions of a large, random sample of vehicles. Gasoline use is known at the state level from sales tax data, and may be disaggregated to individual air basins. A fuel-based motor vehicle CO inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 15 publications
2
76
0
Order By: Relevance
“…The volumetric air dilution rate determined for each tunnel test from SF 6 measurements and calculations were combined with vehicle counts and measurements of CO, CO 2 , and CH 4 to calculate average vehicle miles traveled per unit of fuel consumed in the tunnels. 9,12 Gasoline density of 0.7 g mL Ϫ1 and gasoline carbon content of 0.83 g per gram of fuel were assumed, similar to other studies. 9 Increases in concentrations (g m Ϫ3 ) of species between the tunnel inlet and outlet were converted to emission rates.…”
Section: Testmentioning
confidence: 89%
See 1 more Smart Citation
“…The volumetric air dilution rate determined for each tunnel test from SF 6 measurements and calculations were combined with vehicle counts and measurements of CO, CO 2 , and CH 4 to calculate average vehicle miles traveled per unit of fuel consumed in the tunnels. 9,12 Gasoline density of 0.7 g mL Ϫ1 and gasoline carbon content of 0.83 g per gram of fuel were assumed, similar to other studies. 9 Increases in concentrations (g m Ϫ3 ) of species between the tunnel inlet and outlet were converted to emission rates.…”
Section: Testmentioning
confidence: 89%
“…All NMHC samples collected in tunnel tests (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and parking garage test (PG). Comparison between the collocated sample measurements from each laboratory was used to validate the data.…”
Section: Methodsmentioning
confidence: 99%
“…Correlations were also observed between ASM test results and remote sensing measurements of the same sample of vehicles, grouped by model year (8). In studies of emissions variability by driving mode (14,15), mild to moderate loads similar to that encountered on the ASM generally result in HC, CO and NO X emissions that are lower than those encountered at higher loads. Under lower loads and decelerations, HC is typically higher and NO X is lower than at ASM-type loads.…”
Section: Resultsmentioning
confidence: 99%
“…Conversion to mass emission rates was necessary for the estimation of total mass emission reductions. The calculation, described in detail elsewhere (8,14,15) uses a carbon balance to relate reported pollutant exhaust concentrations (ppm HC, ppm NO X , %CO, %CO 2 ) to the total carbon content of the fuel. Typical fuel properties were used to normalize emissions to fuel consumption.…”
Section: Approachmentioning
confidence: 99%
“…In the present study, a fleet average ratio of EC to particulate organic compounds from on-road diesel vehicles first was computed from the literature review of diesel engine emissions characteristics as a function of production era reported by Sawyer and Johnson 44 combined with estimates of relative annual mileage accumulation by trucks and autos of different ages. 45,46 The analysis suggests that diesel engine emissions in the South Coast Air Basin surrounding Los Angeles in 1993 should consist of ϳ33% EC and 31% organic compounds by mass, plus trace amounts of Si and Al, as measured in diesel exhaust by Hildemann and co-workers. 26 The combined diesel engine profile used in the present study thus consists of EC, Al, Si, and total organics in those proportions, with the relative composition of the organic compounds taken from the GC/MS analysis of filter samples taken during the source tests of Hildemann and co-workers.…”
Section: Bacterial Mutation Assaymentioning
confidence: 99%